2015
DOI: 10.1007/s10072-015-2252-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of metastasis-associated protein 3 in human brain glioma related to tumor prognosis

Abstract: Glioma represents a disparate group of tumors characterized by high invasion ability, and therefore it is of clinical significance to identify molecular markers and therapeutic targets for better clinical management. Previously, metastasis-associated protein family (MTA) is considered to promote tumor cell invasion and metastasis of human malignancies. Recently, the newly identified MTA3 has been shown to play conflicting roles in human malignancies, while the expression pattern and potential clinical signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…MTA3 presented the highest fold change in normal and glioma tissues (Figure B). MTA3 has been reported to be a tumor inhibitor in several tumors, including glioma . Thus, we chose MTA3 for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…MTA3 presented the highest fold change in normal and glioma tissues (Figure B). MTA3 has been reported to be a tumor inhibitor in several tumors, including glioma . Thus, we chose MTA3 for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, limited publications indicated that MTA3 might play conflicting roles compared with the other two MTA members [22]. The expression level of MTA3 was found to be down-regulated in human brain glioma and closely correlated to clinicopathologic characteristics and outcome of patients [23]. While in human brain glioma cell lines, knockdown of MTA2 expression was found to could significantly suppress tumor cell growth, migration and invasion [24].…”
Section: Discussionmentioning
confidence: 99%
“…MTA3 is underexpressed in glioma [99], ovarian cancer [100], and endometrial cancer [101]. MTA3 expression was reported to be associated with differentiation [13], cancer progression [14], and overall survival rates [14, 99].…”
Section: Association Of Mta3 With Emt and Metastasis In Cancersmentioning
confidence: 99%
“…MTA3 expression was reported to be associated with differentiation [13], cancer progression [14], and overall survival rates [14, 99]. Given that the malignancies such as glioma, ovarian cancer, and endometrial cancer have nature of invasive and migration, further studies are required to elucidate how MTA3 regulates the EMT and metastasis in these cancers.…”
Section: Association Of Mta3 With Emt and Metastasis In Cancersmentioning
confidence: 99%